Inovasi Pajak Dalam Peningkatan Kepatuhan Wajib Pajak Di Indonesia - Rebecca Evadine; Dina Rosmaneliana; Dumariani Silalahi; Harlen Silalahi; Berlin Barus (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to provide an overview of the efforts by the Directorate General of Taxes in Indonesia, focusing on innovations in information technology aimed at enhancing taxpayer compliance to support sustainable national development and improve the welfare of the Indonesian people. The research employs a literature review method with a tax-innovative approach. The findings reveal that tax innovations have yielded two distinct effects on taxpayer compliance. While the tax amnesty did not significantly impact compliance, the implementation of electronic systems had a substantial positive effect. This research contributes valuable insights into the importance of analyzing the impact of tax innovations. The data and information used in this study are sourced from media publications, seminars, and books that are included in the data center of the Directorate General of Taxes in Indonesia.